2019
DOI: 10.1111/birt.12426
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of common practices for identifying substance use during pregnancy in obstetric clinics

Abstract: Background: Substance use during pregnancy has been linked to adverse birth and other outcomes. Screening and intervention in the prenatal clinic are recommended, and reliance on patient reports or selective urine drug screening is inadequate. The aim of this prospective project was to determine substance use identification rates associated with common screening practices, compared to universal screening, among pregnant women seeking care at an urban, academic obstetric clinic. Methods: Women attending their f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…5 Individual studies from the United States have estimated it even higher (19%-31%) based on urine analyses. 22,24,25 One of these studies also found prevalences of nicotine of 17%, alcohol 19.4%, opioids 4.0%, cocaine 0.8%, amphetamines 1.2%, and benzodiazepines 1.0%. 22 Recent Danish studies show varying alcohol prevalence estimates: 0.4% for heavy exposure, 3 3% for weekly intake, 26 and up to 35% for binge drinking.…”
Section: Discussionmentioning
confidence: 97%
“…5 Individual studies from the United States have estimated it even higher (19%-31%) based on urine analyses. 22,24,25 One of these studies also found prevalences of nicotine of 17%, alcohol 19.4%, opioids 4.0%, cocaine 0.8%, amphetamines 1.2%, and benzodiazepines 1.0%. 22 Recent Danish studies show varying alcohol prevalence estimates: 0.4% for heavy exposure, 3 3% for weekly intake, 26 and up to 35% for binge drinking.…”
Section: Discussionmentioning
confidence: 97%
“…Further, as the intention of the parent trial was to study a behavioral intervention to reduce secondhand smoke exposure, several variables previously associated with breastfeeding were not measured. For example, we did not capture data on alcohol and drug use, due in part to the challenges of universal drug screening with pregnant women (or new mothers) especially in states with punitive or adverse outcomes (e.g., child custody investigations) for mothers who test positive at delivery ( 46 ). Further, the setting of this study (Houston, Texas, US) is important to consider, as Texas lacks several statutes (e.g., breastfeeding friendly infant-feeding policies in hospitals ( 47 )) associated with increased breastmilk feeding at discharge, placing Texas among states with lower proportions of very low birth weight (<1500g) infants discharged on breastmilk ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Eight articles discussed disparities in detection based on the CDC social vulnerability domain of household characteristics. 33,37,38,[41][42][43][44][45] Seven articles included findings indicating disparities in detection based on age. 33,37,38,41,[43][44][45] Four of these seven articles found younger individuals were more likely to receive uTox than older individuals.…”
Section: Household Characteristicsmentioning
confidence: 99%
“…33,37,38,[41][42][43][44][45] Seven articles included findings indicating disparities in detection based on age. 33,37,38,41,[43][44][45] Four of these seven articles found younger individuals were more likely to receive uTox than older individuals. 37,41,43,45 In one of the seven studies, providers self-reported that younger age was associated with an increased likelihood of uTox among their patients.…”
Section: Household Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation